Carbon nanotube with good conductivity and preparation method thereof

Through the combination of modified magnesium-aluminum hydrotalcite carrier and n-butyric acid, combined with sodium borohydride reaction, the existing carbon nanotube preparation methods and poor conductivity are solved, and the carbon nanotubes with high efficiency are achieved. Meets the needs of high-quality applications.

CN119263265AInactive Publication Date: 2025-01-07SHANDONG ANNENGTAI OIL & GAS STIMULATION TECH RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638091.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carbon nanotube preparation methods are cumbersome, time-consuming and poor conductivity, making it difficult to meet the application needs of high-quality requirements, especially in the conductive industries with high conductivity, electrode conductivity and light transmittance.

Method used

Modified magnesium-aluminum hydrotalcite is used as the catalyst support, and the dispersion of metal particles and the exposure of active sites through the combination of sodium 3-aminobenzenesulfonate intercalation and the combination of n-butyric acid is improved, and the in-situ reduction reaction of sodium borohydride is combined. Achieve efficient growth of single-wall carbon nanotubes with good conductivity.

Benefits of technology

It improves the conductivity and purity of carbon nanotubes, reduces the content of metal impurities, ensures the uniformity of pipe diameter and length, and enhances its application potential in the field of conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263265A_ABST
    Figure CN119263265A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive materials, in particular to a carbon nanotube with good conductivity and a preparation method thereof. The preparation raw materials of the carbon nanotube comprise the following components: hydrocarbon and a catalyst. Modified magnesium-aluminum hydrotalcite is used as a catalyst carrier, n-butyric acid is added, and metal particles are bonded through ionic bonds and coordinate bonds, so that the metal particles are stably and uniformly loaded on the carrier, the catalytic activity is improved, and growth of high-magnification single-walled carbon nanotubes is realized; and the uniform tube diameter and length of the generated carbon nano tube are ensured, the length-diameter ratio is increased, and the prepared carbon nano tube is good in conductivity and high in purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive materials, and in particular to a carbon nanotube with good conductivity and a preparation method thereof. Background Art

[0002] Carbon nanotubes (CNTs) are one-dimensional quantum materials with special structures. Their radial dimensions can reach nanometers, their axial dimensions are micrometers, and both ends of the tubes are generally sealed. The interconnected carbon atom layers are curled into a tubular structure with diameters ranging from one nanometer to tens of nanometers, and the longest length can reach several centimeters. As an excellent conductive material, carbon nanotubes have shown great potential for application in the fields of electronics, energy, and communications. At present, the commonly used carbon nanotube preparation methods reported in the prior art mainly include: arc discharge method, chemical vapor deposition method, laser evaporation method, template method, etc. How to prepare carbon nanotubes with high purity and few structural defects is a prerequisite for in-depth research and application. How to obtain a preparation method with easy operation, low production cost, high raw material utilization rate, few structural defects, and high purity requires further in-depth research; the lack of some carbon atoms in the production and preparation makes the prepared carbon nanotubes contain more defects, which reduces their conductivity, thereby limiting their application in fields with high quality requirements for carbon nanotubes. However, the existing preparation method is still relatively complicated and time-consuming. In addition, the conductivity of the prepared carbon nanotubes is still poor, which makes it difficult to meet the requirements of the conductive industry, electrode conductive industry, conductive industry with high light transmittance and other fields. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a carbon nanotube with good electrical conductivity and a preparation method thereof.

[0004] The present invention is achieved through the following technical solutions: A carbon nanotube with good electrical conductivity. The raw materials for preparing the carbon nanotube include the following components: hydrocarbon and catalyst.

[0005] Furthermore, the hydrocarbon is at least one of methane, ethylene, acetylene, propylene and ethane.

[0006] Furthermore, the preparation method of the catalyst comprises the following steps: (1) Magnesium chloride hexahydrate and sodium aluminate (Na2Al2O2) are dissolved in deionized water to obtain solution A and solution B respectively, solution A and solution B are mixed evenly, sodium hydroxide aqueous solution and sodium carbonate aqueous solution are added in sequence, reacted at 500-600 rpm and 80-90°C for 30-40 min, cooled to room temperature, filtered, the filter cake is washed with deionized water, and vacuum dried at 100°C for 4-5 h to obtain magnesium aluminum hydrotalcite; (2) adding sodium 3-aminobenzenesulfonate to deionized water, stirring at 300-400 rpm for 10 min, adding the magnesium aluminum hydrotalcite obtained in step (1), introducing nitrogen and continuing stirring at 35° C. for 2 h, filtering with suction, washing the filter cake with deionized water, and drying at 70° C. to obtain modified hydrotalcite; (3) Add n-butyric acid to deionized water and mix well to obtain a n-butyric acid solution. Mix the modified hydrotalcite obtained in step (2) with the n-butyric acid solution, stir at 200 rpm for 30-40 min, then dropwise add the metal solution at a rate of 0.5-1 mL / min while stirring. After the dropwise addition is completed, continue stirring for 30 min. Add sodium borohydride aqueous solution dropwise. After the dropwise addition is completed, continue stirring for 1 h. Filter with suction, and vacuum dry the filter cake at 25° C. and a vacuum degree of -0.09 MPa for 8 h to obtain a catalyst.

[0007] Furthermore, in step (1), the mass concentration of magnesium chloride hexahydrate in deionized water in the solution A is 0.3-0.5 g / mL.

[0008] Furthermore, in step (1), the mass concentration of sodium aluminate in deionized water in solution B is 0.06-0.1 g / mL.

[0009] Furthermore, in step (1), the concentration of the sodium hydroxide aqueous solution is 4.5-7.5 mol / L.

[0010] Furthermore, in step (1), the concentration of the sodium carbonate aqueous solution is 0.3-0.5 mol / L.

[0011] Furthermore, in step (1), the volume ratio of deionized water to the sodium hydroxide aqueous solution and the sodium carbonate aqueous solution used in the solution A and the solution B is 1:1:1:1.

[0012] Furthermore, in step (2), the ratio of sodium 3-aminobenzenesulfonate to deionized water is 1 g: 15-20 mL.

[0013] Furthermore, in step (2), the mass ratio of the sodium 3-aminobenzenesulfonate to the magnesium aluminum hydrotalcite is 1:10-12.

[0014] Furthermore, in step (3), the mass concentration of n-butyric acid in deionized water in the n-butyric acid solution is 8-12 mg / mL.

[0015] Furthermore, in step (3), the mass ratio of the modified hydrotalcite to n-butyric acid is 8:1.

[0016] Furthermore, in step (3), the method for preparing the metal solution comprises the following steps: adding ferric nitrate, cobalt nitrate and nickel nitrate to deionized water, stirring at 300-400 rpm for 20 min to obtain a metal solution, wherein the mass concentrations of ferric nitrate, cobalt nitrate and nickel nitrate in deionized water are 0.015-0.02 g / mL, 0.04-0.05 g / mL and 0.02-0.03 g / mL, respectively.

[0017] Furthermore, in step (3), the mass concentration of sodium borohydride in deionized water in the sodium borohydride aqueous solution is 0.04-0.06 g / mL.

[0018] Furthermore, in step (3), the mass ratio of ferric nitrate to n-butyric acid is 1:2.

[0019] Furthermore, in step (3), the mass ratio of ferric nitrate to sodium borohydride is 2:0.8-1.2.

[0020] Furthermore, the present invention also provides a method for preparing the carbon nanotubes with good conductivity, comprising the following steps: placing a catalyst in a tubular furnace, introducing nitrogen until the oxygen content in the tubular furnace reaches 0.2wt%, replacing the nitrogen with a hydrocarbon gas at a gas flow rate of 1 L / min, heating the tubular furnace to 750-800°C at a rate of 30°C / min, keeping the temperature for 2.5-3 h, stopping heating and passing gas, introducing nitrogen at a flow rate of 1 L / min, and continuously cooling to a tubular furnace temperature of 60-80°C to obtain carbon nanotubes with good conductivity.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses modified magnesium aluminum hydrotalcite as a catalyst carrier. The magnesium aluminum hydrotalcite has active groups such as hydroxyl groups, has a large surface energy, an unstable surface structure, and is prone to hydrogen bonding to form agglomeration, resulting in uneven particle size, which affects the catalytic effect. The present invention intercalates sodium 3-aminobenzenesulfonate with magnesium aluminum hydrotalcite. Sodium 3-aminobenzenesulfonate is loaded between hydrotalcite layers with sulfonic acid groups. The sulfonic acid group intercalation changes the interlayer spacing of the hydrotalcite. The sulfonic acid group has a strong charge density, which can increase the electrostatic repulsion between the layers, further preventing the occurrence of agglomeration, and making the catalyst material better dispersed. The modified carrier can effectively disperse the metal catalytic active components and increase the exposure density of the catalytic active sites; introduce functional groups to provide a richer coordination environment, and more efficiently produce coordination with the metal active components. The present invention uses modified hydrotalcite as a carrier to load metal particles, and at the same time adds butyric acid. The carboxyl group of the butyric acid, the amino group of the sodium 3-aminobenzenesulfonate and the metal particles are bonded by ionic bonds and coordination bonds, -COO - and -NH3 + The electrostatic attraction is generated by the difference in surface charge properties, -COO- There is a lone pair of electrons on the hydroxyl oxygen in the -NH3, which enters the empty orbit of the metal particle to form a covalent coordination bond; + The N atoms in the catalyst also have lone pairs of electrons, which can also provide lone pairs of electrons to form coordination bonds with metal particles, thus forming a stable triangular bonding form, so that the metal particles are stably and evenly loaded on the carrier. After the in-situ reduction reaction with sodium borohydride, the leaching of metal particles can be effectively reduced, the dispersion of active centers can be improved, the agglomeration of metal particles can be reduced, the active sites of the catalyst can be increased, the utilization rate of the metal active sites can be higher, the catalytic activity can be improved, and the growth of single-walled carbon nanotubes with a high rate can be achieved; the stable loading of the metal particles by the modified magnesium-aluminum hydrotalcite can limit the migration and aggregation of the metal, avoid the agglomeration of metal particles, the metal particles are evenly distributed on the carrier, and the carbon nanotubes can be continuously deposited and grown for a long time, thereby ensuring that the diameter and length of the generated carbon nanotubes are uniform, the aspect ratio is increased, the conductivity of the carbon nanotubes is improved, and the carbon nanotubes have a high rate and a low content of metal impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 This is a transmission electron microscope image of the carbon nanotubes described in Example 1 of the present invention; Figure 2 The resistivity test graph of the carbon nanotubes described in Examples 1-3 and Comparative Examples 1-2 of the present invention; Figure 3 This is a grayscale test diagram of the carbon nanotubes after calcination described in Examples 1-3 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention are purchased through commercial channels.

[0025] Embodiment 1: This embodiment provides a carbon nanotube with good electrical conductivity. The raw materials for preparing the carbon nanotube include the following components: ethylene and a catalyst.

[0026] The method for preparing a catalyst comprises the following steps: (1) Take 50 g of magnesium chloride hexahydrate and 10 g of Na2Al2O4 and dissolve them in 100 mL of deionized water to obtain solution A and solution B respectively. Mix solution A and solution B evenly, add 100 mL of 7.5 mol / L sodium hydroxide aqueous solution and 100 mL of 0.5 mol / L sodium carbonate aqueous solution in sequence, react at 600 rpm and 90°C for 40 min, cool to room temperature, filter, wash the filter cake with deionized water, and vacuum dry at 100°C for 5 h to obtain magnesium aluminum hydrotalcite; (2) 1 g of sodium 3-aminobenzenesulfonate was added to 20 mL of deionized water, and the mixture was stirred at 400 rpm for 10 min. Then, 12 g of the magnesium aluminum hydrotalcite obtained in step (1) was added, nitrogen was introduced, and stirring was continued at 35° C. for 2 h. The mixture was filtered, and the filter cake was washed with deionized water and dried at 70° C. to obtain a modified hydrotalcite. (3) Take 2 g of ferric nitrate, 5 g of cobalt nitrate and 3 g of nickel nitrate and add them to 100 mL of deionized water, stir at 400 rpm for 20 min to obtain a metal solution, add 1.2 g of n-butyric acid to 100 mL of deionized water and mix well to obtain a n-butyric acid solution, mix 9.6 g of the modified hydrotalcite obtained in step (2) with the n-butyric acid solution, stir at 200 rpm for 40 min, then add 30 mL of the metal solution dropwise at a rate of 1 mL / min while stirring, continue stirring for 30 min after the addition is complete, add 6 mL of a 0.06 g / mL sodium borohydride aqueous solution dropwise, continue stirring for 1 h after the addition is complete, filter, and vacuum dry the filter cake at 25°C and a vacuum degree of -0.09 MPa for 8 h to obtain a catalyst.

[0027] This embodiment also provides a method for preparing the carbon nanotubes with good conductivity, comprising the following steps: placing 1 g of a catalyst in a tubular furnace, introducing nitrogen until the oxygen content in the tubular furnace reaches 0.2 wt%, replacing the nitrogen with ethylene gas at a gas flow rate of 1 L / min, heating the tubular furnace to 800°C at a rate of 30°C / min, keeping the temperature for 3 h, stopping heating and passing gas, introducing nitrogen at a flow rate of 1 L / min, and continuously cooling to a tubular furnace temperature of 80°C to obtain carbon nanotubes with good conductivity.

[0028] Embodiment 2: This embodiment provides a carbon nanotube with good electrical conductivity. The raw materials for preparing the carbon nanotube include the following components: acetylene and a catalyst.

[0029] The method for preparing a catalyst comprises the following steps: (1) Take 30 g of magnesium chloride hexahydrate and 6 g of Na2Al2O4 and dissolve them in 100 mL of deionized water to obtain solution A and solution B respectively. Mix solution A and solution B evenly, add 100 mL of 4.5 mol / L sodium hydroxide aqueous solution and 100 mL of 0.3 mol / L sodium carbonate aqueous solution in sequence, react at 500 rpm and 80°C for 30 min, cool to room temperature, filter, wash the filter cake with deionized water, and vacuum dry at 100°C for 4 h to obtain magnesium aluminum hydrotalcite; (2) 1 g of sodium 3-aminobenzenesulfonate was added to 15 mL of deionized water, and the mixture was stirred at 300 rpm for 10 min. Then, 10 g of the magnesium aluminum hydrotalcite obtained in step (1) was added, nitrogen was introduced, and stirring was continued at 35° C. for 2 h. The filter cake was washed with deionized water and dried at 70° C. to obtain a modified hydrotalcite. (3) 1.5 g of ferric nitrate, 4 g of cobalt nitrate and 2 g of nickel nitrate were added to 100 mL of deionized water and stirred at 300 rpm for 20 min to obtain a metal solution. 1.2 g of n-butyric acid was added to 150 mL of deionized water and mixed to obtain a n-butyric acid solution. 9.6 g of the modified hydrotalcite obtained in step (2) was mixed with the n-butyric acid solution and stirred at 200 rpm for 30 min. Then, 40 mL of the metal solution was added dropwise at a rate of 0.5 mL / min while stirring. After the addition was completed, stirring was continued for 30 min. 6 mL of a 0.04 g / mL sodium borohydride aqueous solution was added dropwise. After the addition was completed, stirring was continued for 1 h. The filter cake was vacuum dried at 25°C and a vacuum degree of -0.09 MPa for 8 h to obtain a catalyst.

[0030] This embodiment also provides a method for preparing the carbon nanotubes with good conductivity, comprising the following steps: placing 1 g of catalyst in a tubular furnace, introducing nitrogen until the oxygen content in the tubular furnace reaches 0.2wt%, replacing the nitrogen with acetylene gas at a gas flow rate of 1 L / min, heating the tubular furnace to 750°C at a rate of 30°C / min, keeping the temperature for 2.5 h, stopping heating and passing gas, introducing nitrogen at a flow rate of 1 L / min, and continuously cooling to a tubular furnace temperature of 60°C to obtain carbon nanotubes with good conductivity.

[0031] Embodiment 3: This embodiment provides a carbon nanotube with good electrical conductivity. The raw materials for preparing the carbon nanotube include the following components: propylene and a catalyst.

[0032] The method for preparing a catalyst comprises the following steps: (1) Take 40 g of magnesium chloride hexahydrate and 8 g of Na2Al2O4 and dissolve them in 100 mL of deionized water to obtain solution A and solution B respectively. Mix solution A and solution B evenly, add 100 mL of 6 mol / L sodium hydroxide aqueous solution and 100 mL of 0.4 mol / L sodium carbonate aqueous solution in sequence, react at 550 rpm and 85°C for 35 min, cool to room temperature, filter, wash the filter cake with deionized water, and vacuum dry at 100°C for 4.5 h to obtain magnesium aluminum hydrotalcite; (2) 1 g of sodium 3-aminobenzenesulfonate was added to 18 mL of deionized water, and the mixture was stirred at 350 rpm for 10 min. Then, 11 g of the magnesium aluminum hydrotalcite obtained in step (1) was added, nitrogen was introduced, and stirring was continued at 35° C. for 2 h. The mixture was filtered, and the filter cake was washed with deionized water and dried at 70° C. to obtain a modified hydrotalcite. (3) 1.8 g of ferric nitrate, 4.5 g of cobalt nitrate and 2.5 g of nickel nitrate were added to 100 mL of deionized water and stirred at 350 rpm for 20 min to obtain a metal solution. 1.08 g of n-butyric acid was added to 100 mL of deionized water and mixed to obtain a n-butyric acid solution. 8.64 g of the modified hydrotalcite obtained in step (2) was mixed with the n-butyric acid solution and stirred at 200 rpm for 35 min. Then, 30 mL of the metal solution was added dropwise at a rate of 0.8 mL / min while stirring. After the addition was completed, stirring was continued for 30 min. 5.4 mL of a 0.05 g / mL sodium borohydride aqueous solution was added dropwise. After the addition was completed, stirring was continued for 1 h. The filter cake was vacuum dried at 25°C and a vacuum degree of -0.09 MPa for 8 h to obtain a catalyst.

[0033] This embodiment also provides a method for preparing the carbon nanotubes with good conductivity, comprising the following steps: placing 1 g of a catalyst in a tubular furnace, introducing nitrogen until the oxygen content in the tubular furnace reaches 0.2 wt%, replacing the nitrogen with propylene gas at a gas flow rate of 1 L / min, heating the tubular furnace to 780°C at a rate of 30°C / min, keeping the temperature for 2.8 h, stopping heating and passing gas, introducing nitrogen at a flow rate of 1 L / min, and continuously cooling to a tubular furnace temperature of 70°C to obtain carbon nanotubes with good conductivity.

[0034] The difference between Comparative Example 1 and Example 1 is that, in the preparation method of the catalyst, the magnesium aluminum hydrotalcite prepared in step (1) is used to react with the metal solution, that is, step (2) is not included in this comparative example and no n-butyric acid is added in step (3) for reaction. The comparative example specifically comprises the following steps: 9.6 g of the magnesium aluminum hydrotalcite prepared in step (1) of the catalyst preparation method of Example 1 is added to 100 mL of deionized water, stirred at 200 rpm for 40 min, 30 mL of the metal solution is added dropwise at a rate of 1 mL / min while stirring, stirring is continued for 30 min after the addition is completed, 6 mL of a 0.06 g / mL sodium borohydride aqueous solution is added dropwise, stirring is continued for 1 h after the addition is completed, and suction is filtered. The filter cake is vacuum dried at 25° C. and a vacuum degree of -0.09 MPa for 8 h to obtain a catalyst.

[0035] The only difference between Comparative Example 2 and Example 1 is that in the method for preparing the catalyst, n-butyric acid is not added in step (3).

[0036] Experimental Example 1: The carbon nanotubes prepared in Example 1 were examined by transmission electron microscopy. Figure 1 As shown, the results are Figure 1 shown.

[0037] Figure 1 The results show that the carbon nanotubes in Example 1 have good uniformity, thin tube diameters, mainly concentrated in the range of 8-10 nm, and tube lengths of 20-30 μm. The carbon nanotubes prepared in Example 1 of the present invention have a relatively high aspect ratio and are more easily overlapped to form a conductive network. The conductivity of the carbon nanotubes is related to the length of their tube diameters. The longer the carbon nanotubes and the smaller the tube diameters, the better the conductivity of the carbon nanotubes, indicating that the carbon nanotubes of the present invention have good conductivity.

[0038] Experimental Example 2: The conductivity of the carbon nanotubes of Examples 1-3 and Comparative Examples 1-2 was tested according to the method of GB / T1410-2006 to measure their resistivity. The measurement results are shown in FIG. Figure 2 shown.

[0039] Figure 2 The results show that the resistivity of the carbon nanotubes in Examples 1-3 is lower than that in Comparative Examples 1-2, indicating that the catalyst carrier of the present invention fixes the metal ions, is not easy to agglomerate, increases the catalytic active sites, improves the catalytic activity, ensures that the diameter and length of the generated carbon nanotubes are uniform, and improves the conductivity of the carbon nanotubes. The carbon nanotubes of the present invention have good conductivity.

[0040] Experimental Example 3: Weigh 0.2 g of each of the carbon nanotubes prepared in Examples 1-3, place them in 100 mL beakers, add 25 mL of aqua regia and heat to 200°C for digestion, filter the digestion solution to constant volume, and then measure the metal impurities by ICP-OES. The results are shown in Table 1; in addition, take 10 g of the carbon nanotubes in Examples 1-3 and Comparative Example 1-2 and place them in a muffle furnace, keep them at a constant temperature of 900°C for 4 h, measure the weight of the calcined residue after cooling, and calculate the ash content (%). The results are shown in Table 1. Figure 3 shown.

[0041] Table 1: Metal impurity content of carbon nanotubes

[0042] Table 1 and Figure 3 The results show that the carbon nanotubes of Examples 1-3 have low Fe, Co, and Ni metal impurity contents, and the ash content of Examples 1-3 is lower than that of Comparative Examples 1-2, indicating that the carbon nanotubes of the present invention have low metal impurity contents and high purity.

[0043] Experimental Example 4: The carbon nanotubes prepared in Examples 1-3 and Comparative Examples 1-2 were taken out from the tube furnace and weighed, and the growth rate was calculated. The obtained data is shown in Table 2.

[0044] Table 2: Carbon nanotube growth rate

[0045] The results in Table 2 show that the growth rate of the carbon nanotubes in Examples 1-3 is higher than that in Comparative Examples 1-2, indicating that the carbon nanotubes of the present invention have a large growth rate and a high yield.

[0046] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A carbon nanotube with good electrical conductivity, wherein the raw materials for preparing the carbon nanotube include the following components: a hydrocarbon compound and a catalyst; The hydrocarbon is at least one of methane, ethylene, acetylene, propylene and ethane; The method for preparing the catalyst comprises the following steps: (1) Dissolving magnesium chloride hexahydrate and Na2Al2O2 in deionized water to obtain solution A and solution B respectively, mixing solution A and solution B evenly, adding sodium hydroxide aqueous solution and sodium carbonate aqueous solution in sequence, reacting at 500-600 rpm and 80-90° C. for 30-40 min, standing and cooling, filtering, washing the filter cake, and vacuum drying to obtain magnesium aluminum hydrotalcite; (2) adding sodium 3-aminobenzenesulfonate to deionized water, stirring, adding the magnesium aluminum hydrotalcite obtained in step (1), introducing nitrogen and continuing to stir, filtering with suction, washing the filter cake, and drying to obtain a modified hydrotalcite; (3) adding n-butyric acid to deionized water and mixing to obtain n-butyric acid solution; mixing the modified hydrotalcite obtained in step (2) with the n-butyric acid solution; adding the metal solution dropwise while stirring; continuing to stir after the addition is complete; adding sodium borohydride aqueous solution dropwise; continuing to stir after the addition is complete; filtering with suction; and vacuum drying the filter cake to obtain a catalyst.

2. The carbon nanotube with good conductivity according to claim 1, characterized in that: In step (1), the mass concentration of magnesium chloride hexahydrate in deionized water in solution A is 0.3-0.5 g / mL; the mass concentration of sodium aluminate in deionized water in solution B is 0.06-0.1 g / mL; the concentration of the sodium hydroxide aqueous solution is 4.5-7.5 mol / L; the concentration of the sodium carbonate aqueous solution is 0.3-0.5 mol / L; and the volume ratio of deionized water used in solution A and solution B to the sodium hydroxide aqueous solution and the sodium carbonate aqueous solution is 1:1:1:

1.

3. The carbon nanotube with good conductivity according to claim 2, characterized in that: In step (2), the dosage ratio of the sodium 3-aminobenzenesulfonate to deionized water is 1 g:15-20 mL; the mass ratio of the sodium 3-aminobenzenesulfonate to magnesium aluminum hydrotalcite is 1:10-12.

4. The carbon nanotube with good conductivity according to claim 3, characterized in that: In step (3), the mass concentration of n-butyric acid in deionized water in the n-butyric acid solution is 8-12 mg / mL; and the mass ratio of modified hydrotalcite to n-butyric acid is 8:

1.

5. The carbon nanotube with good conductivity according to claim 4, characterized in that: In step (3), the method for preparing the metal solution comprises the following steps: adding ferric nitrate, cobalt nitrate and nickel nitrate to deionized water, stirring at 300-400 rpm for 20 min to obtain a metal solution, wherein the mass concentrations of ferric nitrate, cobalt nitrate and nickel nitrate in deionized water are 0.015-0.02 g / mL, 0.04-0.05 g / mL and 0.02-0.03 g / mL, respectively.

6. The carbon nanotube with good conductivity according to claim 5, characterized in that: In step (3), the mass concentration of sodium borohydride in deionized water in the sodium borohydride aqueous solution is 0.04-0.06 g / mL; the mass ratio of ferric nitrate to n-butyric acid is 1:2; and the mass ratio of ferric nitrate to sodium borohydride is 2:0.8-1.

2.

7. A method for preparing carbon nanotubes with good conductivity as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: The catalyst is placed in a tubular furnace, nitrogen is introduced, and the nitrogen is replaced with hydrocarbon gas. The tubular furnace is heated to 750-800°C at a rate of 30°C / min. After keeping the temperature for 2.5-3 hours, the heating and gas flow are stopped, nitrogen is introduced at a flow rate of 1 L / min, and the temperature is continuously cooled to 60-80°C in the tubular furnace to obtain carbon nanotubes with good conductivity.